Diamond enriched lamination and winding insulation for electrical machines. Issue 4 (1st July 2019) - Szucs, Aron; Kolondzovski, Zlatko; Westerlund, Jan; Vahala, Juha
Abstract : Purpose: The thermal management of electrical insulations poses a challenge in electrical devices as electrical insulators are also thermal insulators. Diamond is the best solid electrical insulator and thermal conductor. This can lead to a paradigm change for electrical machine winding and lamination insulation design and thermal management. The paper introduces these techniques and discusses its effect for the design of electrical machines and its potential consequences for electromagnetic analysis, for example, in multi-physics modelling. The diamond winding insulation is patent-pending, but the diamond enriched lamination insulation is published for the benefit of the scientific community. Design/methodology/approach: The windings of electrical machines are insulated to avoid contact between the coil and other conductive components, for example, the stator core. The principle of using mica tape and resin impregnation has not changed for a century and is well established to produce main insulation on a complex conductor shape and size. These insulations have poor heat-conducting properties. Similarly, the insulation of laminated steel sheets comprising the stator and rotor restrict heat flow. Diamond-based insulation provides a new path. Increased thermal conductivity means reduced temperature rise and the reduced thermal time constants in multi-physics simulations and system analysis. Findings: The largest benefit of a diamond-based core insulation is in electrical machines in which the losses are conducted axially to the coolant. These are machines with radial ducts and effective cooling in the end regions. The main benefit will be in reducing the number of radial ducts that positively affect the size, production costs and the copper losses of the machine. The increased thermal conductivity of the diamond insulation system will reduce the thermal constants noticeably. These will affect system behavior and the corresponding simulation methods. Originality/value: Diamond insulation can lead to a paradigm change for electrical machine winding and lamination insulation design and thermal management. It might also lead to new modeling requirements in system analysis.